Substrate Specificity and Expression of Three 2,3-Dihydroxybiphenyl 1,2-Dioxygenases from Rhodococcus globerulus Strain P6 - McKay, David B. (American Society for Microbiology, 2003)
Rhodococcus globerulus strain P6 contains at least three genes, bphC1, bphC2, and bphC3, coding for 2,3-dihydroxybiphenyl 1,2-dioxygenases; the latter two specify enzymes of the family of one-domain extradiol dioxygenases. In order to assess the importance of these different isoenzymes for the broad catabolic activity of this organism towards the degradation of polychlorinated biphenyls (PCBs), the capacities of recombinant enzymes expressed in Escherichia coli to transform different chlorosubstituted dihydroxybiphenyls formed by the action of R. globerulus P6 biphenyl dioxygenase and biphenyl 2,3-dihydrodiol dehydrogenase were determined. Whereas both BphC2 and BphC3 showed similar activities for 2,3-dihydroxybiphenyl and all monochlorinated 2,3-dihydroxybiphenyls, BphC1 exhibited only weak activity for 2′-chloro-2,3-dihydroxybiphenyl. More highly chlorinated 2′-chlorosubstituted 2,3-dihydroxybiphenyls were also transformed at high rates by BphC2 and BphC3 but not BphC1. In R. globerulus P6, BphC2 was constitutively expressed, BphC1 expression was induced during growth on biphenyl, and BphC3 was not expressed at significant levels under the experimental conditions. Although we cannot rule out the expression of BphC3 under certain environmental conditions, it seems that the contrasting substrate specificities of BphC1 and BphC2 contribute significantly to the versatile PCB-degrading phenotype of R. globerulus P6.